The mixed‐valent 10‐manganese(III/IV)‐containing 36‐tungsto‐4‐arsenate(V), [MnIII6MnIV4O4(OH)12(H2O)12(A‐β‐AsW9O34)4]22−. Issue 11 (26th October 2018) - Al-Oweini, Rami; Bassil, Bassem S.; Itani, Marwa; Emiroğlu, Dilara Börte; Kortz, Ulrich
Abstract : The mixed‐valent 10‐managanese‐containing 36‐tungsto‐4‐arsenate(V) [Mn III 6 Mn IV 4 O4 (OH)12 (H2 O)12 ( A ‐β‐AsW9 O34 )4 ] 22− was synthesized in a one‐pot reaction in aqueous medium and characterized as a mixed potassium–sodium salt in the solid state by FT–IR spectroscopy and single‐crystal XRD, as well as elemental and thermogravimetric analyses. Abstract : Interaction of the mixed‐valent 12‐manganese coordination complex [Mn III 8 Mn IV 4 O12 (CH3 COO)16 (H2 O)4 ] with the lacunary 9‐tungstoarsenate(V) [ A ‐α‐AsW9 O34 ] 9− resulted in the 10‐manganese(III/IV)‐containing 36‐tungsto‐4‐arsenate(V), [Mn III 6 Mn IV 4 O4 (OH)12 (H2 O)12 ( A ‐β‐AsW9 O34 )4 ] 22− (1 ). Polyanion1 was isolated as a hydrated mixed potassium–sodium salt, K14 Na8 [Mn III 6 Mn IV 4 O4 (OH)12 (H2 O)12 ( A ‐β‐AsW9 O34 )4 ]·104H2 O, which crystallizes in the orthorhombic space group Pbcn and was characterized by FT–IR spectroscopy and single‐crystal X‐ray diffraction, as well as elemental and thermogravimetric analyses. The title polyanion contains a unique [Mn III 6 Mn IV 4 O4 (OH)12 (H2 O)12 ] 14+ core stabilized within the 36‐tungsto‐4‐arsenate(V) framework.